COLONIAL LEGACIES AND COMPETING MASCULINITIES: THE SUPREME COURT OF CANADA’S RETURN TO REASON IN R. V. KAPP - Hodes, Caroline (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2017)
This article examines a series of unarticulated gender dynamics that shaped some of the recent changes to the legal test for discrimination under s. 15 of the Canadian Charter of Rights and Freedoms. Despite the volume of literature that references R. v. Kapp, none of it has specifically addressed how race is gendered through the claims of the accused, the witnesses who testified on their behalf or the decisions of the judges who interpreted their testimony. Revisiting the legal strategies used in this case reveals ongoing challenges to accessing justice for marginalized groups and impediments to reconciliation.